Pengembangan Media Pembelajaran 3 Dimensi “Rolling Ball Game” Pada Mata Pelajaran Akidah Akhlak di Madrasah Tsanawiyah - Aulia, Dika; Ramadhani, Nurul (Indonesian Journal of Islamic Educational Review, 2024)
This article discusses the development of the 3-dimensional learning medium "rolling ball game" in the Aqidah Akhlak subject at the One Roof Tsanawiyah Madrasah Datok Sulaiman Palopo. This research aims 1) to determine the stages of development of the 3-dimensional "rolling ball game" in the Aqidah Akhlak subject at Madrasah Tsanawiyah Satu Atap Datok Sulaiman Palopo, 2) to determine the validity of the development of the 3-dimensional "rolling ball game" in the Aqidah Akhlak subject at Madrasah Tsanawiyah One Roof Datok Sulaiman Palopo, and 3) to find out students' responses to the development of the 3-dimensional "rolling ball game" in the Aqidah Akhlak subject at Madrasah Tsanawiyah One Roof Datok Sulaiman Palopo. This type of research is R&D (research and development). Researchers use the ADDIE development model with five stages, including analysis, design, development, implementation, and evaluation. This research was conducted at the One Roof Tsanawiyah Madrasah Datok Sulaiman Palopo. The subjects of this research were students in VIII A for the 2023/2024 academic year. The data collection techniques in this research were expert validation sheets and student response questionnaires. The data analysis techniques used are qualitative descriptive analysis and quantitative descriptive analysis. The results of this research indicate that 3-dimensional learning media meet the criteria for being very valid for use in teaching Aqidah Akhlak. The results of the validation of the 3-dimensional learning media "rolling ball game," namely media expert validation, obtained a percentage of 77, 5% with appropriate criteria, material expert validation obtained a percentage of 93,18% with very appropriate criteria, and language expert validation obtained a percentage of 75% with the criteria worthy. In the questionnaire, student responses obtained a percentage of 85, 25% in the very positive category.